ANALISIS PERSAINGAN ANTAR TOKO OLEH-OLEH DI YOGYAKARTA DALAM PRESPEKTIF HUKUM PERSAINGAN USAHA - Berlyana Putri; Rosalinda Elsina Latumahina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Business activities that can lead to business competition between actors in the field of business can create a broad market and create a democratic market so as to give rise to increasingly fierce business competition. Trade competition is carried out to win the hearts of buyers. Trade on-screen characters attempt to offer alluring items, both in concerning cost, quality and advantage. Of course, the company competes with other competitors to be identified, monitored and tricked in order to obtain and maintain customer loyalty. Business competition carried out by the perpetrators is getting tighter. In this case the Head of Regional Office VII of the Business Competition Supervisory Commission (KPPU) sensed unfair business competition behavior related to the sale of souvenirs located in the Special Region of Yogyakarta, indications of unfair business competition practices were in the form of closed agreements between shops selling souvenirs to visitors who want to travel in Yogyakarta. The indication is that there is a business entity that prohibits suppliers from supplying goods to other business entities and threatens suppliers. This study aims to analyze the suitability of the form of sanctions imposed by the KPPU on souvenir shops that violate them. The inquire about strategy utilized in this ponder is the standardizing juridical law investigate strategy with a statutory approach and a conceptual approach. The comes about of this ponder KPPU can force these regulatory sanctions in total or then again. In any case, within the common clarification of Law no. 5 of 1999 expressed that the Commission is as it were authorized to force authoritative sanctions, whereas the court is authorized to force criminal sanctions. A case dealt with by KPPU can at that point be handed over to examiners and so can be sentenced to a criminal sentence